If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(a-1)+2(a+1)=9
We move all terms to the left:
3(a-1)+2(a+1)-(9)=0
We multiply parentheses
3a+2a-3+2-9=0
We add all the numbers together, and all the variables
5a-10=0
We move all terms containing a to the left, all other terms to the right
5a=10
a=10/5
a=2
| 2(a+4)+3(a+1)=46 | | 9x-2(3x-2)=5(x-2) | | 1/10y-5=-19 | | -2=4/5x=6 | | 7-x÷8=6 | | 26x+43=5(8x+3) | | 12d-4=-7 | | -4x+5=-4x-4−4x+5=−4x−4 | | z÷10-1=5 | | x=90-(4x+12) | | n/4=12n= | | 4(v-1)=-9v-30 | | x=90-(4+12) | | 5(v+8)-8v=28 | | v/2-15=21 | | 3y-2=6(y-1)-3y | | 69.6=6(m+3.2 | | 8n=-40n= | | 14=-8u+2(u-8) | | 6x−6=15x+15 | | 105.3=9(m+2.9) | | -1z+5=7 | | 4x/2+10/5=20 | | 20w+100=400 | | 15=x/3=8 | | 72=6(m+3.7) | | −75x+57=−75x+57 | | -24=-6p/7 | | 10+200+10x=1000-69x | | 4n-7=5n | | 5−6(x+4)=15 | | 1768=34(p+10) |